Understanding the business of global media in the Digital Age - Lee, Micky; Jin, Dal Yong 1964- (Routledge, Taylor & Francis Group, 2018)
"This new introductory textbook provides students with the tools they need to understand the way digital technologies have transformed the global media business of the 21st century. Focusing on three main approaches - media economics, critical political economy, and production studies - the authors provide an empirically rich analysis of ownership, organizational structures and culture, business strategies, markets, networks of strategic alliances, and state policies as they relate to global media. Examples throughout involve both traditional and digital media and are taken from different regions and countries to illustrate how the media business is influenced by interconnected historical, political, economic, and social factors. In addition to introducing today's convergent world of global media, the book gives readers a greater understanding of their own potential roles within the global media industries"--Provided by publisher.